(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Blockchain technology is as a decentralized, distributed ledger that stores, records and analyze the source of digital information and assets. Blockchain is a Distributed Ledger Technology (DLT), it makes the history of any unalterable digital information and transparent through the use of cryptographic techniques in decentralized hashing method. Example Google Doc is a application of blockchain technology. We create a document and share it with a group of people, the document is distributed instead of copied or transferred. This creates a chain in decentralized distributed chain and any one can access the same time. Any other person is locked out awaiting changes from another party, while all modifications to the documents are being recorded in real-time, making changes completely transparent.1.Digital Information and Assets are not copied or transferred. It is distributed2.The digital asset is decentralized, allowing full real-time access.3.Which creates trust based on transparent ledger4.All the changes preserve integrity of the documentBlockchain is revolutionary technology and provide promising to avoid risk, stamps and fraud level services. It brings transparency in a scalable way for multiple uses.